Cytotoxicity and antiviral activity of methanol extract from Polygonum minus - Noor Zarina, Abd Wahab; Hamidun, Bunawan; Nazlina, Ibrahim (2015)
A study was carried out to test the cytotoxicity and antiviral effects of methanolic extracts from the leaves and stem of Polygonum minus or kesum. Cytotoxicity tests were performed on Vero cells indicates the LC50 value for leaf extract towards the Vero cells was 875 mg/L and the LC50 value for stem extract was 95 mg/L. The LC50 values indidcate the non-cytotoxic effect of the extracts and worth for further testing. Antiviral test were carried out towards herpes simplex virus infected Vero cells using three concentration of extract which were equivalent to 1.0 LC50, 0.1 LC50 and 0.01 LC50. Three different treatments to detect antiviral activity were used. Mild antiviral activity of the stem extract was detected when cells were treated for 24 hours with plant extract before viral infection. This demonstrates the capability of the test compound to protect the cells from viral attachment and of the possible prophylactic effect of the P. minus stem methanol extract.